2021
DOI: 10.1108/ijopm-07-2020-0485
|View full text |Cite
|
Sign up to set email alerts
|

Big data analytics in digital platforms: how do financial service providers customise supply chain finance?

Abstract: PurposeThis study examines the role of financial service providers (FSPs) in assessing the supply chain credit of small and medium-sized enterprises (SMEs) and how they help SMEs obtain supply chain finance (SCF) through an established digital platform using big data analytics (BDA).Design/methodology/approachThis study conducted data mining analysis on the archival data of China's FSPs in the mobile production industry from 2015 to 2018, using neural networks in the first stage and multiple regression in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
69
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 73 publications
6
69
0
Order By: Relevance
“…Further studies that corroborate this study have suggested that BDA capability can be used to enhance enterprise agility, especially to predict customers' transactional patterns for tailored services (Stylos et al, 2021). Song et al (2021) also promoted the need for financial institutions to use digital platforms with BDA to potentially identify the risk of borrowers and the quality of customised services.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…Further studies that corroborate this study have suggested that BDA capability can be used to enhance enterprise agility, especially to predict customers' transactional patterns for tailored services (Stylos et al, 2021). Song et al (2021) also promoted the need for financial institutions to use digital platforms with BDA to potentially identify the risk of borrowers and the quality of customised services.…”
Section: Discussionsupporting
confidence: 59%
“…Bolstering various study BDA capability implications for the financial sector (Song et al, 2021;Galhau et al, 2016;Gupta and George, 2016), this study demonstrates the impact of BDA usage on FSA. The findings help financial institutions focus on nurturing technical capabilities of digital technology deployment and strategic managerial capabilities to utilise emerging technologies like BDA applications.…”
Section: Managerial Implication Of the Studysupporting
confidence: 61%
See 3 more Smart Citations